2018
DOI: 10.1073/pnas.1801895115
|View full text |Cite
|
Sign up to set email alerts
|

Gravisensors in plant cells behave like an active granular liquid

Abstract: SignificanceThe sensor of gravity in plants consists of tiny starch-rich grains called statoliths that sediment and form miniature granular piles at the bottom of the gravisensing cells. How such a sensor could be a reliable clinometer is unclear, as granular materials are known to display jamming and finite avalanche angles. Here we address this issue by comparing statolith avalanches in plant cells to microfluidic avalanches of Brownian particles in biomimetic cells. We reveal that statoliths behave like a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 33 publications
(67 reference statements)
3
55
0
Order By: Relevance
“…These observations connect gravitropism with a rapid increase of cytosolic Ca 2+ [ 51 ] and the following conclusion [ 91 ]: “Thus, the identified tight link between the cell wall and cell polarity provides the conceptual possibility for regulation of signal fluxes and, ultimately, plant development via signaling from the extracellular matrix.” Such evidence suggests that auxin-based mechanoperception and subsequent root morphogenesis involve the Hechtian growth oscillator. This fundamental phenomenon supersedes textbook dogma and hypotheses in highly contentious and confusing fields [ 49 , 92 , 93 , 94 ] that struggle to disentangle cause from effect. As a prime example, consider the challenge to identify the gravity sensor.…”
Section: Rootsmentioning
confidence: 86%
“…These observations connect gravitropism with a rapid increase of cytosolic Ca 2+ [ 51 ] and the following conclusion [ 91 ]: “Thus, the identified tight link between the cell wall and cell polarity provides the conceptual possibility for regulation of signal fluxes and, ultimately, plant development via signaling from the extracellular matrix.” Such evidence suggests that auxin-based mechanoperception and subsequent root morphogenesis involve the Hechtian growth oscillator. This fundamental phenomenon supersedes textbook dogma and hypotheses in highly contentious and confusing fields [ 49 , 92 , 93 , 94 ] that struggle to disentangle cause from effect. As a prime example, consider the challenge to identify the gravity sensor.…”
Section: Rootsmentioning
confidence: 86%
“…This phenomenon is reminiscent of the relaxation observed in macroscopic granular materials submitted to external perturbations, such as vibration [11,12], thermal cycling [36], shear below yield stress [37], or fluid-injection below the fluidization threshold [38]. It is also analogous to the mechanism found in the gravity sensing cells of plants, where the gravisensors are made of tiny heavy grains, which are agitated by the cytoskeleton activity to promote their mobility under gravity [39]. To describe this creep regime, we have proposed a one-dimensional thermally activated model based on a Kramers' escape rate.…”
mentioning
confidence: 80%
“…A recent study by Bérut et al [27] showed that statolith sedimentation in gravistimulated endodermal cells quickly responds even to small changes in bending angle. Statoliths therefore behave less like a pile of stones and more like a liquid.…”
Section: Statoliths and The Vacuolar Membranementioning
confidence: 99%
“…It has been hypothesized that cell-generated active (non-Brownian) fluctuations strongly modulate statoliths movements to achieve this effect. Cytoskeletal network dynamics are good candidates for modulating this agitation [27]. Though its regulation has not been linked to changes in the sensitivity of gravitropic responses, it seems possible that local changes in cytoplasmic streaming affect statoliths sedimentation rates.…”
Section: Statoliths and The Vacuolar Membranementioning
confidence: 99%